Transformação de triglicerídeos em combustíveis, materiais poliméricos e insumos químicos: algumas aplicações da catálise na oleoquímica - Suarez, Paulo Anselmo Ziani (2007)
The use of biomass as raw-material for obtaining chemicals, polymers and fuels is emerging as a clever alternative solution for the increasing energy demand, environmental awareness and petroleum shortage. In this work, some attempts in order to develop catalytic systems suitable for triglyceride transformation into fuels, polymers and intermediates are reviewed.